Non-Conviction Based Asset Forfeiture sebagai Upaya Mengoptimalkan Pemulihan Aset Hasil Korupsi - Itok Dwi Kurniawan (ARIMA : Jurnal Sosial Dan Humaniora, 2024)
The aim of writing this article is to analyze the prospects for implementing Non-Conviction Based Asset Forfeiture in the context of recovering assets resulting from corruption. The method used in this research is a normative legal research method. The approach used in writing this article is a statutory approach and a conceptual approach. The results of this research state that Non-Conviction Based Asset Forfeiture is an effective effort to eradicate corruption in Indonesia, especially to recover assets resulting from corruption. Confiscating assets without depending on the defendant's guilt is an effective effort to prevent the escape of assets resulting from corruption by corruptors.